Correlation between plasma myeloperoxidase and hs-troponin I, C-reactive protein and CKMB in acute coronary syndrome - M., Anusha A.; Rajan, Sinju; T., Annamala P.; T., Govindanunni (International Journal of Advances in Medicine, 2020)
Background: Acute coronary syndrome (ACS) is a group of clinical syndromes ranging from unstable angina pectoris to acute myocardial infarction (AMI) and death. Early prediction of ACS is frequently a challenging task. Myeloperoxidase is involved in oxidative stress and inflammation which plays an important role in the pathogenesis and course of ACS. Methods: The study was conducted in 30 male patients in the age group 20 - 80 years who were diagnosed as ACS and admitted to CCU. Twenty age matched normal subjects were taken as controls. Plasma MPO, hsTnI, hsCRP, CKMB, lipid parameters, urea, creatinine, glucose, AST and LDH were estimated in patients and control subjects. Results: Plasma MPO level was found to be 155.5±19.5 ng/ml and 62.4±11.8 in ACS patients and normal controls respectively and that of hsTnI was 133.3±10.1 ng/L and 20.7±1.8 ng/L, hsCRP to be 13.1±1.38 mg/L and 0.51±0.12 mg/L, CKMB to be 166.3±16.7 ng/dl and 12.8±1.51 ng/dl respectively. The values plasma of glucose, cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol, urea and creatinine were found to be slightly elevated in patients but, were not statistically significant when compared to controls. AST and LDH showed statistically significant increase in patients compared to controls. Direct linear correlation was observed between plasma MPO level and hsTnI, hsCRP and CKMB levels. Conclusions: Plasma MPO which is a predictor of early cardiovascular events and also severity of myocardial damage linearly correlates with the values of hsTnI, hsCRP and CKMB.